2011
DOI: 10.1007/s00405-011-1669-9
|View full text |Cite|
|
Sign up to set email alerts
|

Experience with combination of cisplatin plus gemcitabine chemotherapy and intensity-modulated radiotherapy for locoregionally advanced nasopharyngeal carcinoma

Abstract: Addition of induction chemotherapy (IC) to concurrent chemoradiotherapy (CC) is an encouraging first-line treatment strategy for patients with locoregionally advanced nasopharyngeal carcinoma (NPC). We evaluated the clinical efficacy and toxicity of addition of gemcitabine plus cisplatin (GP) IC to intensity-modulated radiotherapy (IMRT) and CC for patients with locoregionally advanced NPC. At a median follow-up duration of 48 months (10-59 months), 4-year local relapse-free survival (LRFS) was 86.9%, regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Gemcitabine combined with cisplatin is an effective combination for the treatment of patients with locoregionally advanced NPC. Ou and coworkers13 reported that 70.3% of those with locally advanced NPC partially responded, whereas 29.7% achieved a complete response after two cycles of a GC regimen before RT. In two other retrospective studies, the overall response rates to the PF regimen, when used as induction chemotherapy, were 88.6 and 91.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gemcitabine combined with cisplatin is an effective combination for the treatment of patients with locoregionally advanced NPC. Ou and coworkers13 reported that 70.3% of those with locally advanced NPC partially responded, whereas 29.7% achieved a complete response after two cycles of a GC regimen before RT. In two other retrospective studies, the overall response rates to the PF regimen, when used as induction chemotherapy, were 88.6 and 91.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The RT method used in our study was conventional. Recently, Xiayun et al 13. reported the use of a combination of GC chemotherapy and IMRT for locoregionally advanced NPC, with encouraging outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OS and DFS of the study group at 3 years was 76% and 63% respectively. With a median follow up of 30 months Xiayun et al (2012) also used gemcitabine and cisplatin both as IC and in adjuvant settings after intensity modulated radiation therapy (IMRT) (Xiayun et al, 2012). With 89% of the patients having stage III-IV, the 3 year OS of the group was 87.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a series of IMRT publications for NPC (Table 2), 13 studies have reported using treatment planning CT with 3 mm or less thickness [5,[20][21][22][23][27][28][29][30][31][32][33][34], one study used 3 to 5 mm which may have been as a result of available technology at the time given that it was the first reported experience [19], while three studies did not report slice thickness [35][36][37]. Therefore, given the available data, we recommend using treatment planning CT with 3 mm or less thickness in areas that contain disease.…”
Section: Treatment Planning and Target Volumesmentioning
confidence: 99%